Amplified electrochemical detection of surface biomarker in breast cancer stem cell using self-assembled supramolecular nanocomposites. (1st September 2018) - Zhao, Jing; Tang, Yingying; Cao, Ya; Chen, Tianshu; Chen, Xiaoxia; Mao, Xiaoxia; Yin, Yongmei; Chen, Guifang
Abstract: Cancer stem cells (CSCs) are recognized as an important source of cancers. Surface biomarkers play a critical role for CSCs profiling and also for diagnostic purposes. In this paper, we propose self-assembled supramolecular nanocomposites assisted multiple signal amplification strategy, and successfully apply it in electrochemical detection of an important CSCs biomarker CD44 as well as identification of breast CSCs. A supermolecular composite, consisting of a binding peptide that is able to bind to the target CD44 and a self-assembled diphenylalanine (FF) nanostructure that provides a template for deposition of gold nanoparticles (AuNPs), is elaborately constructed on the surface of an electrode through the linkage of cucurbit[8]urils. In the presence of CD44, this supramolecule is able to provide amplified electrochemical signals from silver-enhancement on AuNPs after target-protection from trypsin-catalyzed digestion. Whereas in the absence of the target, this supramolecular architecture is destroyed, resulting in suppressed signals. Linear sweep voltammetry results present a satisfactory specificity and sensitivity, which also demonstrate a wide linear range with a limit of detection of 2.17 pg/mL toward CD44 protein and a limit of detection of 8 cells/mL toward CD44-positive cancer cells. Therefore, this work provides a promising prospective for further clinic application in the future. Graphical abstract: Image 1 Highlights: Specific recognition of breast cancer stem cell biomarker CD44 using binding peptide rather than antibody. Signal amplification using supramolecular nanocomposites as a scaffold. Synthesis of self-assembled supramolecular nanocomposites by host-guest interaction. Successful application in sensitively monitoring breast cancer stem cells.